Multimedia Quality About Risk Dating As A Youth Health Promotion Media - Sunartono, Sunartono (Journal of Applied Nursing and Health, 2021)
Background: feeling of liking or being attracted to the opposite sex is often expressed by the term dating. The impact of dating leads to deviant activities such as risky dating. It is important for teenagers to know about risky dating through health promotion activities. The purpose of this study was to determine the quality of multimedia about risky courtship as a medium for adolescent health promotion. Methods: This type of research uses experimental research using an approach R & D. This research method is the assessment of material experts, media experts and small group sample trials with a total of 15 respondents. The research instrument was an open questionnaire which was filled out by the respondents. The analysis used in this study used univariate analysis. Results: Multimedia about risky dating as a health promotion media is said to be feasible by material experts with an average score of 54.33; said to be feasible by media experts with an average score of 50.33 and said to be feasible by users with an average score of 31.13. Conclusion: Multimedia about risky courtship is said to be suitable for use as a media for adolescent health promotion.